Awaken : a journey to purpose, wholeness, and healing - Sisodia, Rajendra (Wiley, 2022)
"The topics of self-awareness and elevating consciousness are subjects of perennial interest. That is especially true in the present times. We are in the midst of a fundamental transition; over the last few years, we have been experiencing multiple awakenings: the "me too" movement, the acknowledgment of systemic racism, the need to rethink capitalism, the elevation of the feminine, the existential threat of climate change, the rapid erosion of our ecosystem and the need for greater global cooperation to combat shared challenges such as pandemics. Along with a growing recognition of these enormous challenges, we have also experienced a steep rise in psychic suffering: anxiety, depression, drug addiction and suicides have all increased significantly. There is a need for a contemporary, easy to understand and easy to implement guide to how each of us can achieve inner peace, healing and a life of purpose. That is what this book is intended to provide"--